Novel Technique Of Modal Analysis On Small Structure Using Piezoelectric Film Sensor And Accelerometer - Ramli, Mohd Irman; Nuawi, Mohd Zaki; Abdullah, Samizee; Mohammad Rasani, Mohammad Rasidi; Md Basar, Mohd Farriz; Ahmad, Muhamad Arif Fadli; Kho, Ko Seng (Asian Research Publishing Network (ARPN), 2017)
Modal Analysis is a common practice to define parameters of structure under scientific view. Experimental Modal Analysis (EMA) is a well-known procedure to determine modal parameters. The usage of piezoelectric film sensor as viable and cost-saving device is indeed a need in this advance and sophisticated era. An experiment is conducted to determine modal parameters of aluminum 6061 (Al6061). Here, a free dynamic vibration analysis is conducted to obtain the parameters. Al6061 is chosen as the experiment component because of its wide application in manufacturing industries. Theoretically, if the component vibrates and produce frequency coherence with the natural frequency, resonance frequency will occur which can lead to structural failure. Modal analysis study is conducted by using both simulation and experimental methods. Simulation is conducted via ANSYS software while impact hammer testing is done for experimental work. Piezoelectric film and accelerometer are used as the sensor. The result obtained from simulation showed that frequencies for mode shape 1, 2 and 3 for square shape are 191.89Hz, 542.34Hz and 766.18Hz. The result gained from accelerometer showed that frequencies for mode shape 1, 2 and 3 for square shape are 195.00Hz, 557.00Hz and 865.00Hz. The result captured from piezoelectric film sensor appeared that frequencies for mode shape 1, 2 and 3 for square shape are 205.33Hz, 609.33Hz and 904.33Hz. The result obtained from simulation showed that frequencies for mode shape 1, 2 and 3 for circle shape were 134.60Hz, 324.73Hz and 727.52Hz. The result obtained from accelerometer showed that frequencies for mode shape 1, 2 and 3 for circle shape were 158.67Hz, 421.33Hz and 625.00Hz. Finally, the result captured from piezoelectric film sensor appeared that frequencies for mode shape 1, 2 and 3 for circle shape were 141.00Hz, 321.00Hz and 504.33Hz respectively. The equation of gradient for accelerometer and piezofilm is ya = 316.42x - 104.13 and yp = 309.63x - 43.20 respectively. Therefore, the relationship between the natural frequency of accelerometer and piezofilm for the square-shaped specimen is ya = 1.02yp - 59.98. The equation of gradient for accelerometer and piezofilm is ya = 270.55x - 134.82 and yp = 280.89x - 215.04 respectively. Therefore, the relation between the natural frequency of accelerometer and piezofilm for the circle-shaped specimen is ya = 0.96yp + 72.3. Both result showed the regression ratio of 1.02 and 0.96 which is approximately 1.0 and there was a good results agreement between simulation and experimental outcome.